2009
DOI: 10.1016/j.jcrs.2009.03.038
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular pressure changes during injection of microincision and conventional intraocular lenses through incisions smaller than 3.0 mm

Abstract: Monitoring during implantation of both IOL types confirmed that IOP increases during insertion, including during microincision surgery using a wound-assisted technique. Further studies are necessary to evaluate the effect of pressure spikes on the optic nerve during IOL insertion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…The elevated IOP during IOL injection might be the initial cause of conjunctiva non-perfusion. In fact, the change of IOP during IOL implantation through a 1.9-2.5 mm incision has been documented in previous studies on cadaver or live eyes [5][6][7]. Kamae et al recorded a biphasic pattern of IOP elevation during IOL injection.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…The elevated IOP during IOL injection might be the initial cause of conjunctiva non-perfusion. In fact, the change of IOP during IOL implantation through a 1.9-2.5 mm incision has been documented in previous studies on cadaver or live eyes [5][6][7]. Kamae et al recorded a biphasic pattern of IOP elevation during IOL injection.…”
Section: Discussionmentioning
confidence: 89%
“…Kamae et al recorded a biphasic pattern of IOP elevation during IOL injection. The first phase of IOP elevation occurred during the optic entering the eye and the second phase occurred when the trailing haptic was pushed into the eye [5]. Kamae et al also found that the peak IOP during IOL injection might as high as 115 mmHg (double of the retinal perfusion pressure) in a successful attempt and 306 mmHg in an unsuccessful attempt [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For individual patients, the duration, frequency and intensity level of episodes of activities in which patients engage, and other factors that are not evident from the raw survey screening responses would need to be considered. For example, although all eye rubbing elevates IOP to potentially pathological levels, the intensity of eye rubbing (and associated level of IOP elevation) can vary widely 17,19,20 as can the frequency and duration of rubbing episodes. Similarly, participation in yoga or other forms of exercising are more significant when horizontal or inverted body positions are assumed and even more so when strenuous muscular effort and altered breathing are involved.…”
Section: Discussionmentioning
confidence: 99%
“…Stretching of the retina and choroid associated with scleral thinning and expansion usually becomes increasingly obvious at higher levels of myopia. Scleral thinning Eye rubbing: elevations up to 300 mmHg 42 and 400 mmHg. 43 Short duration (30 minutes) supine positions: mean elevation of 4.4 mmHg.…”
Section: Scleral Viscoelasticitymentioning
confidence: 99%